Nutrient management for cassava-based cropping systems in Northern Vietnam - Thai Phien; Nguyen Cong Vinh (International Center for Tropical Agriculture, 1998)
Five soil types on which cassava is being planted were investigated. Almost all these soils are degraded in terms of soil properties, especially with respect to soil fertility. Cassava is traditionally planted without fertilizer application and soil conservation measures, resulting in a negative nutrient balance.